Processing of Action and Sound Verbs in Context: An FMRI Study - Popp, Margot (Transl Neurosci, 2019)
Recent theories propose a flexible recruitment of sensory and motor brain regions during conceptual processing depending on context and task. The present functional magnetic resonance imaging study investigated the influence of context and task on conceptual processing of action and sound verbs. Participants first performed an explicit semantic context decision task, in which action and sound verbs were presented together with a context noun. The same verbs were repeatedly presented in a subsequent implicit lexical decision task together with new action and sound verbs. Thereafter, motor and acoustic localizer tasks were administered to identify brain regions involved in perception and action. During the explicit task, we found differential activations to action and sound verbs near corresponding sensorimotor brain regions. During the implicit lexical decision task, differences between action and sound verbs were absent. However, feature-specific repetition effects were observed near corresponding sensorimotor brain regions. The present results suggest flexible conceptual representations depending on context and task. Feature-specific effects were observed only near, but not within corresponding sensorimotor brain regions, as defined by the localizer tasks. Our results therefore only provide limited evidence in favor of grounded cognition theories assuming a close link between the conceptual and the sensorimotor systems.